2021
DOI: 10.1021/acsbiomaterials.1c00780
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Entrapment of His-Tagged Enzymes on Superparamagnetic Zirconium-Based MOFs with Robust Renewability to Enhance pH and Thermal Stability

Abstract: Metal–organic frameworks (MOFs), as a kind of poriferous nanoparticle, are promising candidates for enzyme immobilization to enhance their stability and reusability. However, most MOFs could not specifically immobilize enzymes and regenerate easily, which inevitably leads to serious high consumption and environmental pollution. In this study, renewable and magnetic MOFs were first constructed to specially immobilize His-tagged enzymes from the cell lysates without purification. The immobilized β-glucuronidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Likewise, UiO67@Rh@UiO66 exhibited a higher selectivity in capturing His-tagged LDH when the cell lysate was used (Figure c). These results confirmed that His-tagged LDH was successfully specifically immobilized on UiO67@Rh@UiO66, which was due to the interaction between surface unsaturated Zr­(IV) and the imidazole ring of the histidine in His-tagged LDH . Then, UiO67@Rh@UiO66@LDH was characterized by PXRD, FTIR, ζ potential, and N 2 adsorption and desorption.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Likewise, UiO67@Rh@UiO66 exhibited a higher selectivity in capturing His-tagged LDH when the cell lysate was used (Figure c). These results confirmed that His-tagged LDH was successfully specifically immobilized on UiO67@Rh@UiO66, which was due to the interaction between surface unsaturated Zr­(IV) and the imidazole ring of the histidine in His-tagged LDH . Then, UiO67@Rh@UiO66@LDH was characterized by PXRD, FTIR, ζ potential, and N 2 adsorption and desorption.…”
Section: Resultssupporting
confidence: 65%
“…These results confirmed that His-tagged LDH was successfully specifically immobilized on UiO67@Rh@UiO66, which was due to the interaction between surface unsaturated Zr(IV) and the imidazole ring of the histidine in His-tagged LDH. 47 Then, UiO67@Rh@UiO66@LDH was characterized by PXRD, FTIR, ζ potential, and N 2 adsorption and desorption. In the PXRD pattern (Figure 5d), the crystal structure of the UiO67@Rh@UiO66@LDH did not change significantly compared with UiO67@Rh@UiO66, only the peak intensity was reduced to a certain extent.…”
Section: Chemoenzyme Coupling Systemsmentioning
confidence: 99%
“…At present, enzyme immobilization via multipoint covalent attachment is a big issue: not only solving the problem of separation, it recovers the catalytic activity, specificity, or selectivity, , explicitly the enantio-selectivity over the native enzymes, , but advances the enzyme stability against the fluctuation of temperature, , pH, solvent parameters, and reaction conditions. Immobilized enzymes get hold of a suitable enzymatic microenvironment in porous media; in such microenvironments, intermolecular-inactivation processes have never been experienced, which come into view either for precipitation or proteolysis or interaction with external hydrophobic interfaces. , Second, increasing the enzyme rigidity via covalent binding, particularly multipoint attachment, prevents any conformational change or the subunit dissociation of multimeric proteins ,,, that brings the stability of the immobilized proteins, sometimes even better over their native form.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ahmed et al (2018) successfully fabricated Cellulase@UiO-66-NH 2 , which exhibited a significant improvement in tolerance of temperature, pH, reusability and lifetime. Immobilization is an effective tool for enzyme preservation and continuous operation ( Siar et al, 2017 ; Alagoz et al, 2021 ; Wei et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized immobilized lipase-proline showed a 135% increase in catalytic activity and 4-fold improvement of thermal stability compared to the free enzyme. Wei et al (2021) first constructed renewable and magnetic MOFs (immobilized β-glucuronidase), and the immobilized enzymes exhibited greater stability over a wide range of temperatures and pH. Liang et al (2021) noted that immobilized enzymes to hydrophilic ZIF-90 or MAF-7 could maintain enzyme activity, even when exposed to harsh reaction environment.…”
Section: Introductionmentioning
confidence: 99%